EDUKASI TATA KELOLA DAN PENGEMBANGAN BISNIS MELALUI METODE SPIN-OFF - Roy Setiawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Education in governance and business development has a very important role in ensuring the success and continuity of business in an increasingly complex and dynamic market. Governance and business development education helps individuals to develop the managerial skills necessary to manage resources effectively, make informed decisions, and lead teams efficiently. This education provides an in-depth understanding of various risks associated with business and helps in developing effective risk management strategies. This allows organizations to better anticipate, prevent and manage risks. Governance and business development education helps individuals and organizations to deeply understand market trends, consumer behavior and competitive dynamics. This allows them to develop appropriate strategies to win the competition and expand market share. Education in governance and business development drives innovation and product development that can help organizations stay relevant and competitive in an ever-evolving marketplace. This involves an understanding of market needs and the ability to develop innovative solutions. This education enables organizations to develop more efficient operational processes, increase productivity, reduce costs, and improve service quality. Through proper education in governance and business development, individuals and organizations can gain the knowledge, skills and understanding necessary to face the complex challenges of the modern business world, and effectively achieve sustainable growth and long-term success